Employee Performance at LLDIKTI Region XV: Effect of Work Motivation, Employee Placement and Job Satisfaction - Lenggu, Mesker; Kase, Petrus; Sayrani, Laurensius P (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine and analyze the influence of work motivation, employee placement and job satisfaction on employee performance at Region XV Higher Education Service Institutions. The research that will be carried out uses quantitative research. The results of this research indicate that employee placement has a significant effect on employee performance at LLDIKTI Region XV. Work Motivation has a significant effect on Employee Performance at LLDIKTI Region XV. Job Satisfaction has a significant effect on Employee Performance at LLDIKTI Region XV. Work motivation, employee placement and job satisfaction together have a significant effect on Employee Performance at LLDIKTI Region XV.